In-plane mechanical properties of birch plywood. (18th July 2022) - Wang, Tianxiang; Wang, Yue; Crocetti, Roberto; Wålinder, Magnus
Highlight: In-plane mechanical properties of birch plywood are experimentally determined. An exhaustive dataset on strength and elastic properties of birch plywood in tension, compression, and shear has been established. High load-to-face-grain angle dependency is observed for each property. Analytical models that show sufficient closeness to the test data are suggested. Abstract: There is an increasing demand for engineered wood products in modern structures. Birch plywood is promising in structural applications, due to the combined advantages of its superior mechanical properties and the cross lamination configuration. However, the off-axis mechanical properties of birch plywood have not been thoroughly investigated. The aim of this paper is to establish a comprehensive experimental dataset that could serve as the input in the analytical or numerical models to design birch plywood under various load conditions. Specifically, tensile, compressive and shear tests were conducted under five different angles to the face grain, i.e., from 0° (parallel) to 90° (perpendicular) to the face grain, with an interval of 22.5°. The stress–strain relationships, failure modes, strength and elastic properties of birch plywood are highly dependent on the load-to-face-grain angle. The strength and the elastic properties are also predicted by various analytical and empirical models. Parametric analyses are performed to study the influence of the interaction coefficient F 12 in Tsai-Wu failure criterion and the Poisson's ratio ν x y in the transformation model on the predicted strength and modulus respectively. Lastly, the possibilities of predicting the on-axis shear modulus based on the off-axis uniaxial tests are discussed in this paper.